Optical System for Bispectral Imaging in Mid-IR at 1000 Frames per Second. (13th March 2013) - Strojnik, Marija; Paez, Gonzalo
Abstract : We propose, evaluate, and demonstrate the performance of an IR/optical double-image experimental setup where we capture two simultaneous images of a single object, in two different spectral bands, using a single detector array. With this arrangement, we may observe rapidly changing phenomena, at a rate of more than 1000 frames per second, without the loss of the spatial information about the test subject. We describe the optical system to perform simultaneous imaging in IR for slightly inclined optical axes. We verify the actual performance by applying the experimental method to flame analysis in the mid-IR to determine the combustion efficiency.